Foreign direct investment and environmental taxes - Roberto A. De Santis; Frank Stähler (European Central Bank (ECB), 2008)
This paper studies the effect of foreign direct investment (FDI) on environmental policy stringency in a two-country model with trade costs, where FDI could be unilateral and bilateral and both governments address local pollution through environmental taxes. We show that FDI does not give rise to ecological dumping because the host country has an incentive to shift rents away from the source country towards the host country. Environmental policy strategies and welfare effects are studied under the assumption that parameter values support FDI to be profitable.
Keywords: F12; F18; F23; 330; environmental taxes; Foreign Direct Investment; multinational enterprises; plant location; Auslandsinvestition; Ökosteuer; Steuerwirkung; Multinationales Unternehmen; Transaktionskosten; Betriebliche Standortwahl; Zwei-Länder-Modell; Theorie